Perancangan Dan Pengembangan Mesin Pemisah Kulit Ari Kedelai Otomatis - Muh Farid Hidayatullah; Arya Mahendra Sakti; Sudirman Rizki Ariyanto; Lailatus Sa'diyah Yuniar Arifianti (CV. SINAR HOWUHOWU, 2026)
The soybean processing process for making tempeh for middle- and lower-class soybeans still uses traditional methods to peel and separate the soybean hulls. This machine is designed to address the problem of peeling and separating soybean hulls at the household and lower-middle-scale businesses, which is still often done traditionally (by treading or soaking manually), which is inefficient, unhygienic, and labor-intensive. The main objective of this research is to design and build an automatic soybean peeling and separating machine that is easily accessible, energy-efficient, and able to improve the cleanliness of the processed product. The final design uses a two-geared cylinder mechanism with a gap adjustment (slider) that can be adjusted according to soybean size. Automatic separation utilizes mass/air differences to push the hulls out and the beans fall into a separate channel. The manufacturing process involved literature review, observation, selection of alternative designs, component fabrication, and machine assembly. The expected results are a hopper with a capacity of 15 kg, an electric motor drive with a V-belt pulley transmission, two geared cylinders, and testing of optimal gap variations and cylinder rotations, capable of producing a capacity of approximately 300 kg/hour of clean, ready-to-process soybeans. The design of the hull peeling and separating machine features a peeling mechanism that utilizes the gap between a toothed cylinder and an adjustable adjustment mechanism that adapts to the type of soybean being peeled.